Presencia y distribución de ácaros eriófidos en camelias del sur de Galicia y norte de Portugal - Mansilla Vázquez, J. P.=700 1 Pérez Otero, R.; Salinero Corral, C.; López Villarreal, M. J.; Barrote M. Meira, M. C. R.
Resumenes (Es, En)
Fig; 12 ref.
Keywords: ACAROS ERIOFIDOS; CAMELLIA; DISTRIBUCION DE LA POBLACION; ACAPHYLLA STEINWEDENI; CALACARUS CARINATUS; COSETACUS CAMELLIAE